Surgical Resection of Hepatoblastoma: Factors Affecting Local Recurrence - Younes, Alaa; Elgendy, Ahmed; Fadel, Sayed; Romeih, Marwa; Elwakeel, Madeeha; Salama, Asmaa; Azer, Magda; Ahmed, Gehad (European Journal of Pediatric Surgery, 2020)
Introduction This study aimed to investigate potential factors contributing to local recurrence after surgical resection of hepatoblastoma (HB).Materials and Methods This retrospective study involving all patients with HB who underwent nontransplant surgery at our tertiary center between July 2007 and July 2018. Data were analyzed regarding microscopic surgical resection margin, tumor multifocality and extracapsular tumor extension in correlation with local recurrence. These relations were assessed by logistic regression.Results The study included 133 patients with a median age of 1.3 years (range: 0.5–12.8 years). They were classified into 99 cases (74.44%) standard risk and 34 cases (25.56%) high risk. Delayed surgical resection was adopted in all patients. Follow-up to July 2019 revealed that 23 patients (23/133, 17.3%) developed local recurrence, whereas the remaining 110 were locally disease free. Microscopic positive margin (R1) was detected in 29 patients, 8 of them had local recurrence (p = 0.097). Regarding tumor multifocality, there were 12 patients who had multifocal lesions, 3 of them developed local recurrence (p = 0.459). Forty-four patients had extracapsular tumor extension in their pathological reports, 12 of them had local recurrence (p = 0.032).Conclusion Extracapsular tumor extension was a significant prognostic factor of local recurrence after surgical resection of HB. R1 margin does not necessarily require a second resection, and it could achieve accepted results when combined with adjuvant platinum-based chemotherapy. However, patients who are not eligible for surgical resection must be transferred for primary transplantation to obtain favorable outcome.
Keywords: hepatoblastoma; children; surgical resection; local recurrence; extracapsular tumor extension